1996 Seimas elections and the development of Lithuania's party system - Jūratė Novagrockienė (Politologija)
This article investigates several aspects to which 1996 Seimas elections contribute. The author argues that these elections confirmed certain tendencies in the development of the party system as well as attached new features to it. Aspects that have led to both a short-run victory of the conservative and the Christian democratic parties, and a long-run perspective – emergence of a multiparty system, are being researched profoundly. First of them displays the following points: amendments to the Law of Seimas Elections, their influence on the electoral behaviour of the parties and the suffragettes. The second point is the indices that have articulated certain division of the electoral votes.